Salvador e suas influências Bantu: as fusões culturais que se aprende e ensina no registro da história e da memória - Barros, Fernanda Lícia de Santana (2014)
Salvador and their Bantu influences: cultural fusions that learns and teaches in recorded history and the memory of this theme is research conducted in the city of Salvador, which seeks to investigate the Bantu influences of African descent in most neighborhoods. In Salvador the term Bantu is more commonly referred to Congo-Angola nation in soteropolitano imaginary. Importantly, this is not a job that will be searched or orishas nkisis, but the influences that that nation exercises in Salvador with its symbolism and tangible and intangible heritage, which contribute to teaching and learning supporters and followers contributing to the local history and memory are maintained. The research is qualitative, hemerografica (with use of major newspapers in Salvador) with emphasis on participatory research, making use of oral history. Oral history is being a methodological appeal as the basis of African religions, as in the yards orality is of fundamental importance that his followers learn to hold religious precepts in individual memory, collective memory and religious practices, as well as in memory of each district that were part of this work, being very common each bring their individual and collective history in shaping the city of Salvador. The research problem presents itself expressed in the question: What influences Bantu can be identified in the city of Salvador. Along with the goals is to identify the influences Bantu make up the city of Salvador; Discuss the importance of the religious heritage and history in memory of Salvador. List the main elements that characterize the Bantu culture through the yard, emphasizing their contribution while tangible and intangible heritage, decent education for their adherents and followers.